Coupled Brittle and Viscous Micromechanisms Produce Semibrittle Flow, Grain‐Boundary Sliding, and Anelasticity in Salt‐Rock. Issue 2 (11th February 2021) - Ding, J.; Chester, F. M.; Chester, J. S.; Shen, X.; Arson, C.
Abstract: The operation of fracture, diffusion, and intracrystalline‐plastic micromechanisms during semibrittle deformation of rock is directly relevant to understanding mechanical behavior across the brittle‐plastic transition in the crust. An outstanding question is whether (1) the micromechanisms of semibrittle flow can be considered to operate independently, as represented in typical crustal strength profiles across the brittle to plastic transition, or (2) the micromechanisms are coupled such that the transition is represented by a distinct rheology with dependency on effective pressure, temperature, and strain rate. We employ triaxial stress‐cycling experiments to investigate elastic‐plastic and viscoelastic behaviors during semibrittle flow in two distinctly different monomineralic, polycrystalline, synthetic salt‐rocks. During semibrittle flow at high differential stress, granular, low‐porosity, work‐hardened salt‐rocks deform predominantly by grain‐boundary sliding and wing‐crack opening accompanied by minor intragranular dislocation glide. In contrast, fully annealed, near‐zero porosity salt‐rocks flow at lower differential stress by intragranular dislocation glide accompanied by grain‐boundary sliding and opening. Grain‐boundary sliding is frictional during semibrittle flow at higher strain rates, but the associated dispersal of water from fluid inclusions along boundaries can activate fluid‐assisted diffusional sliding at lower strain rates. Changes in elastic properties with semibrittle flow largely reflect activation of sliding along closed grain boundaries. Observed microstructures, pronounced hysteresis and anelasticity during cyclic stressing after semibrittle flow, and stress relaxation behaviors indicate coupled operation of micromechanisms leading to a distinct rheology (hypothesis 2 above). Plain Language Summary: Controlled deformation experiments on rock are conducted to develop a general understanding of the mechanical properties of earth materials in the crust. Rock consists of an assemblage of mineral grains in tight contact and undergoes deformation in nature by operation of several microscopic processes that often operate simultaneously. When multiple processes occur, their interaction and combined effects can be complex. In this study, two synthetic salt‐rocks are deformed under cyclic loading at pressures and rates that activate multiple microscopic processes. Recoverable and permanent deformations are measured during the experiments, and deformation features are studied using a microscope after experiments. Our findings document that linked networks of opening cracks along grain boundaries and of sliding cracks along grain boundaries is the main process of deformation; but, deformation inside grains and chemical reactions along grain boundaries with water also are important. We find that with small amount of water and low rates of deformation, the chemical action of water can strongly influence mechanical behavior. Our findings indicate that the interactions between multiple microscopic processes must be considered to describe the mechanical behavior of rock accurately. Key Points: Two synthetic salt‐rocks are deformed in cyclic triaxial‐compression to document interaction between pressure‐dependent and pressure‐independent micromechanisms at the brittle‐plastic transition Semibrittle deformation involves coupled operation of grain‐boundary crack opening, grain‐boundary friction and water‐assisted diffusional sliding, and intragranular dislocation glide Grain‐boundary sliding by water‐assisted diffusion leads to pronounced hysteresis and anelasticity at low strain rates